2022
DOI: 10.1002/pc.26700
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid effect of nanoparticles presence on low‐velocity impact resistance in sandwich panels

Abstract: Considering the massive employment of sandwich panels in multifarious applications, numerous research studies have been conducted on their impact resistance enhancement, one of which, is via simultaneous nanoparticles incorporation including various amounts of silica nanoparticles, clay nanoparticles and carbon nanotubes (CNTs) in to sandwich panels, composed of two glass fiber epoxy composite face sheet and polyvinyl chloride core to render them reinforced. The research objective is to experimentally scrutini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…For example, by creating a microporous structure during the processing operations, PC foams can be advantageous for many structuralize and/or functionalize applications such as thermal insulation, sound absorption, separation media, and so forth. However, the cellular structure was inevitably influenced and even decided by the foaming processing, resulting in different properties of the foamed part 18–21 . Similar to other polymers, PC foams can generally be fabricated via the three most popular foaming operations, that is, batch, extrusion, and injection molding foaming operations, and meanwhile, a blowing agent, which possibly involves physical blowing agents (supercritical CO 2 , nitrogen, and water) and chemical blowing agents, is used for releasing gas and generating the porous structure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, by creating a microporous structure during the processing operations, PC foams can be advantageous for many structuralize and/or functionalize applications such as thermal insulation, sound absorption, separation media, and so forth. However, the cellular structure was inevitably influenced and even decided by the foaming processing, resulting in different properties of the foamed part 18–21 . Similar to other polymers, PC foams can generally be fabricated via the three most popular foaming operations, that is, batch, extrusion, and injection molding foaming operations, and meanwhile, a blowing agent, which possibly involves physical blowing agents (supercritical CO 2 , nitrogen, and water) and chemical blowing agents, is used for releasing gas and generating the porous structure.…”
Section: Introductionmentioning
confidence: 99%
“…Sandwich composite structures with continuous fiber composite face sheets have been found very efficient by the aerospace and automotive industries for impact applications because of their high bending stiffness to mass ratio and impact energy absorption. [11][12][13][14][15] Zhang et al 11 investigated drop mass impact and compression tests after impact on sandwich composite structure with honeycomb core and found a decrease of compression strength up to 25%-30% compared with undamaged sandwich composite. The sandwich composites are subjected to fiber-metal skin delamination, foam core cracking, and skin-core interface debonding.…”
Section: Introductionmentioning
confidence: 99%
“…The sandwich composites are subjected to fiber‐metal skin delamination, foam core cracking, and skin‐core interface debonding 12 . Emamieh et al 13 enhanced the impact contact force of sandwich composites containing polyvinyl chloride core and glass/epoxy composite face sheets up to 18.6% by dispersing 0.3% carbon nanotubes, 1% nano clay, and 3% nanosilica particles in the epoxy matrix. Moghaddam et al 14 observed a significant improvement in impact resistance of sandwich composite made of hybrid carbon/glass fabric and epoxy face sheets and rigid polymer foam core by embedding the shape memory alloy wires between the face sheet layers.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of filler materials at nano and micro levels into epoxy resin seems a reasonable approach to improve mechanical performance of fiber reinforced composite materials. [ 11–13 ]…”
Section: Introductionmentioning
confidence: 99%
“…Addition of filler materials at nano and micro levels into epoxy resin seems a reasonable approach to improve mechanical performance of fiber reinforced composite materials. [11][12][13] Fiber reinforced composites are promising materials for aeronautical, automotive, marine, and construction applications due to their high strength and module, perfect rigidity, high corrosion resistance, and low density. [14] The performance of glass fiber reinforced composites varies depending on the type of glass fiber, matrix materials, and matrix modifier fillers.…”
Section: Introductionmentioning
confidence: 99%